Oral Narrative Genres as Communicative Dialogic Resources and their Correlation to African Short Fiction - Huber, Loreta; Jonaitytė, Evelina (Respectus Philologicus, 2020)
Oral and written storytelling traditions in Africa developed at the same time and influenced each other in many ways. In the twentieth century, the relation between the deeply rooted oral tradition and literary traditions intensified.We aim to reveal literary analysis tools that help to trace ways how oral narrative genres found reflection in African short fiction under analysis. A case study is based on two short stories by women writers, The Rain Came by Grace Ogot and The Lovers by Bessie Head. Images and symbols both, in oral and written traditions in Africa, as well as the way they evolved and extended in a literary genre of short fiction are considered within the framework of hermeneutics, reader reception theory and feminist literary criticism.The results obtained in the study prove that oral narrative genres interact with literary genres, though most importantly, women’s writing as a literary category and images embodied in the short stories play a decisive role and deviation from the images embodied in African oral tradition.